GRAVITATIONAL WAVE TRACK IN THE EARTH'S ELECTROMAGNETIC FIELD - Grunskaya, L. V.; Dorochzkov, V. V.; Isakevich, V. V. (Одеські астрономічні публікації, 2017)
At present the idea of the extracting of the frequencies in the earth's electromagnetic field spectra corresponding to the gravitational radiation frequencies of the double star systems is based equally with the traditional approaches to solve the task of gravitational wave fields recording. In the theoretical plan of this task solving the known possible mechanisms of the electromagnetic fields of the ELF range in the Earth-ionosphere cavity being affected with the gravitational wave radiation of the astrophysical source were analyzed and the two-level model of the excitation oscillations in the near by earth's layer with the gravitational wave field is suggested. The catalogues of the spectra allowing to extract the frequencies associated with the global geodynamic processes and to analyze the type of the spectrum near by the frequencies of the astrophysical sources are arisen from the long- term continuous records of the earth's electromagnetic field with the multiple-response receiving complex of 1997 and 1998 enlisting the correlation and spectral analyses methods and the up-to-date ones of the simulation of the non-linear dynamical processes. The addition of the known methods of the direct recording of the gravitational wave radiation of the astrophysical objects to the suggested electromagnetic phenomena are very useful on account of the theoretically predicted low intensity gravitational wave radiation for the solving of the fundamental problem of the modern physics- the gravitational wave detection.